Literal translation from English and Malay in the written communication among Malay learners of French - Abdul Halim, Hazlina; Abdul Aziz, Adi Yasran; Mamat, Roslina; Abdul Rahim, Normaliza (Canadian Center of Science and Education, 2013)
This study intended to examine the use of literal translation from English and Malay language in the written communication. The objectives were to investigate the most present language used in the translation to French, the use of the literal translation (LT) of Malay and English in the written communication among across gender, and to determine at which sentence level (words, phrase or syntax) the translation was used by the learners. The research utilized qualitative and quantitative methods of data analysis. The study was conducted among Malay non-native speakers of French as a foreign language at Universiti Putra Malaysia. A total of 50 subjects took part in this study. The task was to complete a writing task of 150-200 words after 100 hours of French learning. The results indicated that Malay language played a more important part in the translation, where 163 elements of translation were found as opposed to 76 elements from English language. Among the translations produced by the learners, 57 items were in the word form, 77 items in the phrase form and 105 items in the sentence form. The results of this study could help in the teaching of French to Malay learners by making them aware of literal translation which already in their repertoire and by encouraging them to use the translation effectively.